Analisis Dinamika Faktor Lingkungan Selama Proses Pengkristalan Garam di Greenhouse Salt Tunnel (Studi kasus di Pantai Utara dan Pantai Selatan, Jawat Timur, Indonesia) - Abd Aziz Amin; Adi Tiya Yanuar; Zulkisam Pramudia; Yogita Ayu Dwi Susanti; Ilham Misbakudin AL Zamzami; Lutfi Ni’matus Salamah; Riski Agung Lestariadi; Lukman Hakim; Gatot Ardian; Mokh Hanifuddin; Andi Kurniawan (Jurnal Penelitian Pendidikan IPA, 2025)
Salt is an essential commodity for both domestic use and industrial applications, with East Java Province in Indonesia playing a crucial role in national salt production. Traditional salt production methods, primarily based on natural evaporation, face challenges due to seasonal factors, particularly during the rainy season. This study investigates the environmental conditions affecting the salt crystallization process in the Greenhouse Salt Tunnel (GST) technology. Field experiments were conducted at two sites, Tuban Regency on the North Coast and Malang Regency on the South Coast, where key parameters such as air temperature, water temperature, humidity, wind speed, and evaporation rates were monitored three times daily. The findings showed that water temperatures within the GST ranged from 31 to 38°C on the North Coast and 26 to 38°C on the South Coast. Wind speeds varied between 1.5–2.4 m/s on the North Coast and 0.4–1.0 m/s on the South Coast, while humidity levels ranged from 54 to 80%. The GST system achieved a salt production rate of 6.4 kg/m² with NaCl content exceeding 94%, a significant improvement over traditional methods, which yield less than 70% NaCl. These results demonstrate that GST technology enhances both the quality and quantity of salt production, though design modifications are needed to address the dynamic coastal environment.